2009
DOI: 10.3109/13693780902788621
|View full text |Cite
|
Sign up to set email alerts
|

The still obscure attributes of cryptococcal glucuronoxylomannan

Abstract: Glucuronoxylomannan (GXM) is the major capsular polysaccharide of Cryptococcus neoformans. It is essential for fungal virulence and causes a number of deleterious effects to host cells. During the last decades, most of the experimental models designed to study the roles of GXM during cryptococcal infection were based on the stimulation of animal cells. This most commonly involved macrophages or other effector cells, with polysaccharide fractions obtained by precipitation with cationic detergents. More recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The capsular size is unquestionably important for cryptococcal pathogenicity (28), but other biological and physical chemical properties of capsular components have also been linked to the mechanisms by which C. neoformans interacts with the host (52). Therefore, we evaluated the relevance of APT1 to general properties of extracellular polysaccharides and capsular components of C. neoformans.…”
Section: Deletion Of Atp1 Does Not Affect Global Flippase Activity In Cmentioning
confidence: 99%
“…The capsular size is unquestionably important for cryptococcal pathogenicity (28), but other biological and physical chemical properties of capsular components have also been linked to the mechanisms by which C. neoformans interacts with the host (52). Therefore, we evaluated the relevance of APT1 to general properties of extracellular polysaccharides and capsular components of C. neoformans.…”
Section: Deletion Of Atp1 Does Not Affect Global Flippase Activity In Cmentioning
confidence: 99%
“…vivo (150). Karashima and collaborators reported that T. asahii isolates could switch phenotype and increase the amount of secreted GXM after passage in a mouse model (91).…”
Section: Cell Wall Componentsmentioning
confidence: 99%
“…25,51 The MICs of the echinocandins and azoles corresponded to prominent growth inhibition (approximately 50% inhibition relative to control growth) or a complete growth inhibition in the case of amphotericin B. All the strains were also tested using the E-test susceptibility method, according to the manufacturer's instructions for VRC, PSC, ITZ, FLC, AMB and CFG (bioMerieux SA, 532800, 532100, 525808, 510800, 526300, 532400).…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 99%
“…2,22 It has been speculated that the secretion of proteases and phospholipases are important virulence factors for scavenging nutrient inside the host. 23 These pathogens are also able to produce glucuronoxylomannan (GXM) in their cell walls, similarly to Cryptococcus neoformans 24,25 and it is possible this polysaccharide may help to attenuate phagocytosis by host immune cells. 25 However, there is no genetic evidence about the functionality of these virulence factors.…”
Section: Introductionmentioning
confidence: 99%